2003
DOI: 10.1007/s00438-003-0881-8
|View full text |Cite
|
Sign up to set email alerts
|

An integrated physical and genetic map of the nematode Pristionchus pacificus

Abstract: The free-living nematode Pristionchus pacificus is one of several species that have recently been developed as a satellite system for comparative functional studies in evolutionary developmental biology. Comparisons of developmental processes between P. pacificus and the well established model organism Caenorhabditis elegans at the cellular and genetic levels provide detailed insight into the molecular changes that shape evolutionary transitions. To facilitate genetic analysis and cloning of mutations in P. pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(130 citation statements)
references
References 27 publications
(21 reference statements)
3
127
0
Order By: Relevance
“…Cell-ablation experiments were carried out using standard techniques 27 , by ablating the gonad 0-1 h after hatching of the larvae (20°C). RILs were set up by crossing 3-5 males of RS5275/BOL to 1 virgin hermaphrodite of PS312/CA and heterozygous F1 animals were determined using standard mapping markers 28 (www.pristionchus.org). Heterozygous F1 animals were isolated and, in the F2, single animals were transferred to new plates and allowed to self-fertilize.…”
Section: Methodsmentioning
confidence: 99%
“…Cell-ablation experiments were carried out using standard techniques 27 , by ablating the gonad 0-1 h after hatching of the larvae (20°C). RILs were set up by crossing 3-5 males of RS5275/BOL to 1 virgin hermaphrodite of PS312/CA and heterozygous F1 animals were determined using standard mapping markers 28 (www.pristionchus.org). Heterozygous F1 animals were isolated and, in the F2, single animals were transferred to new plates and allowed to self-fertilize.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence analysis of the polymorphisms indicated that between the polymorphic strains of P. pacificus (PS312 and PS1843), 73.7% were substitutions and 26.3% were insertions/deletions. Of the substitutions, 47.3% were transitions and 52.7% were transversions, a finding that is exactly converse to that of C. elegans (Koch et al, 2000;Srinivasan et al, 2002;Wicks et al, 2001). Data from these polymorphisms provided the necessary prerequisite for further mapping studies to clone genes defined by mutations.…”
Section: Biogeography and Polymorphisms In Pristionchus Pacificusmentioning
confidence: 84%
“…Further understanding of these developmental processes necessitated a genomic framework. Generation of an integrated genetic linkage map and a physical map for mapping of mutants has set a good foundation for such molecular studies (Srinivasan et al, 2003;Srinivasan et al, 2002). With the impending genome sequence being generated by the Washington Genome sequencing center (WUGSC) funded by NHGRI, P. pacificus is bound to cross the 'next frontier' in our understanding of evolution of developmental and behavioral processes.…”
Section: Introductionmentioning
confidence: 99%
“…All markers are incorporated into AppaDB using the marker name and chromosomal coordinates. (9). Since the SSCP markers were mostly generated from BAC ends, the genetic linkage map information of these SSCP tagged BAC clones could be anchored directly on the physical map.…”
Section: Genetic Linkage Map and Stssmentioning
confidence: 99%
“…In recent years, developmental and molecular studies have been complemented by a genomic approach. Speci®cally, a genetic linkage map (8) and a physical map (9) were generated and two large-scale sequencing projects (EST and BAC end sequencing) performed. To compile all the genomic information generated in P.paci®cus, we developed a database called AppaDB that presents all the information in a comprehensive manner.…”
Section: Introductionmentioning
confidence: 99%